Copper-based current collector modified by self-repairing artificial interface layer, preparation method of copper-based current collector and application of copper-based current collector in negative-electrode-free lithium battery
By depositing a self-healing artificial interface layer made by solution polymerization of four functional monomers on the copper-based current collector, the problem of shortening the cycle life of the negative electrode-free lithium battery is solved, and the high cycle performance and rate performance of the battery are achieved.
Patent Information
- Application Number
- CN202411629635.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The cycle life of negative electrode-free lithium batteries is shortened mainly because lithium dendrites pierce the solid electrolyte interface layer (SEI) and cause the SEI layer to continuously break and regenerate, thereby accelerating the irreversible consumption of lithium and electrolyte.
The self-healing artificial interface layer prepared by solution polymerization of four functional monomers was deposited on the copper-based fluid collector by electrophoretic deposition. The interface layer consists of nitrogen-containing water-soluble comonomer, quaternary ammonium salt monomer, double-bonded end-polyethylene oxide and dopamine self-healing monomer, and has good mechanical properties, high ionic conductivity and self-healing. sex.
The cycle performance and rate performance of negative electrode-free lithium batteries are improved, the cycle life of the battery is extended, and multiple hydrogen bonds are formed by the catechol groups of dopamine-based self-healing monomers, realizing timely repair of the interface layer.
Smart Images

Figure CN119481077A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a copper-based current collector modified with a self-repairing artificial interface layer, a preparation method thereof, and an application thereof in a negative electrode-free lithium battery. Background Art
[0002] Recently, the use of lithium metal batteries with single lithium as the negative electrode to replace the existing lithium-ion batteries has attracted attention in the academic community, but the high reactivity of lithium leads to problems such as electrolyte decomposition and dendrite growth piercing the separator. In addition, the preparation of thin lithium foil with equivalent capacity to the positive electrode also faces the challenges of complex process and high cost in industrial production. In view of this, a negative electrode-free lithium battery consisting of a lithium-rich positive electrode and a copper-based current collector negative electrode without metal lithium was proposed.
[0003] The so-called negative electrode-free lithium battery is actually an ideal lithium metal battery in a fully discharged state, that is, the lithium in the initial battery is all stored in the active material on the positive electrode side according to the electrochemical stoichiometric ratio. During the first charge, the lithium migrates from the positive electrode side to the copper-based current collector. This will bring the following problems: (1) The nucleation barrier of lithium on the copper current collector is high, which will greatly reduce the reversibility of lithium deposition / stripping. (2) During the deposition and stripping process, lithium will react with the electrolyte to form a solid electrolyte interface (SEI). The SEI layer has poor mechanical properties, which will cause lithium dendrites to pierce the layer, resulting in continuous rupture and regeneration of the SEI layer, accelerating the irreversible consumption of lithium and electrolyte; and there are a large number of defects in the formed SEI film, which will cause uneven electric field and ion flux, thereby accelerating the uncontrollable growth of lithium dendrites, and ultimately shortening the cycle life of the negative electrode-free lithium battery. Therefore, improving the cycle life and stability of negative electrode-free lithium batteries has become a major challenge at present.
[0004] In order to solve these problems, scientists' research is currently focused on electrolyte optimization, copper-based current collector modification, and control of cut-off voltage / discharge depth. For anode-free lithium batteries, lithium is directly deposited on the surface of the copper-based current collector. The initial nucleation conditions between them directly affect the subsequent deposition behavior of lithium, so the modification of the copper-based current collector is more important. This modification method can not only enhance the interfacial compatibility between lithium and copper-based current collectors, but also inhibit the decomposition of electrolytes and the corrosion of lithium, thereby extending the cycle life of the battery. The reconstruction of copper-based current collectors mainly includes three aspects: setting an artificial interface layer, three-dimensional structure design, and current collector material replacement. Among them, the setting of an artificial interface layer is achieved by coating, polymerization, calcination, etc. on the copper-based current collector. This method can reduce the direct contact between lithium and electrolyte to promote the formation of a stable SEI, and can also reduce the nucleation barrier by regulating the desolvation kinetics of lithium ions. Therefore, in recent years, researchers have become more and more interested in setting an artificial interface layer to build high-performance lithium batteries. Patent CN118198375A discloses that an ultra-thin and ultra-light interface layer composed of DNA is arranged on a copper-based current collector to promote the adsorption of lithium ions. Patent CN117438533A sets an ion layer and a conductive sublayer on the copper-based current collector, which respectively plays the role of reducing the nucleation barrier of lithium ions and inhibiting the excessive reduction and decomposition of the electrolyte, and effectively regulates the deposition and stripping behavior of lithium ions. However, the artificial interface layer reported so far has a single functionality and lacks self-repairing functional monomers, which cannot meet the requirements of long battery cycles. Therefore, it is very necessary to develop a copper-based current collector modified with a self-repairing artificial interface layer. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention discloses a copper-based current collector modified with a self-repairing artificial interface layer and a preparation method thereof. The self-repairing artificial interface layer is prepared by solution polymerization of four functional monomers, which is composed of ionomers with self-repairing functions and is deposited on the copper-based current collector by electrophoretic deposition. The artificial interface layer has good mechanical properties, high ionic conductivity and self-repairing properties, and can improve the cycle performance of a negative electrode-free lithium battery.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a copper-based current collector modified with a self-repairing artificial interface layer, which is obtained by modifying a bare copper-based current collector with a self-repairing functional ionomer prepared by solution polymerization of four components A, B, C, and D, wherein component A is a nitrogen-containing water-soluble comonomer, which is 20 to 45 parts by weight, component B is a quaternary ammonium salt monomer, which is 20 to 40 parts by weight, component C is a double-bond terminated polyethylene oxide, which is 30 to 45 parts by weight, and component D is a dopamine self-repairing monomer, which is 0.5 to 1.0 parts by weight.
[0007] The thickness of the self-repairing artificial interface layer is 5-10 μm.
[0008] The nitrogen-containing water-soluble comonomer is one of acrylamide, N-methyl methacrylamide and methacrylamide.
[0009] The quaternary ammonium salt monomer is one of methacryloyloxyethyl trimethyl ammonium chloride, methacryloyloxypropyl trimethyl ammonium chloride and acryloyloxyethyl trimethyl ammonium chloride.
[0010] The double-bond terminated polyethylene oxide is polyethylene glycol monomethyl ether methacrylate.
[0011] The dopamine self-repairing monomer is 3-methacrylamide dopamine.
[0012] The second aspect of the present invention provides a method for preparing the copper-based current collector modified by the self-repairing artificial interface layer, comprising the following steps.
[0013] Firstly, nitrogen-containing water-soluble comonomers, quaternary ammonium salt monomers, double-bond-terminated polyethylene oxide and dopamine self-healing monomers and part of the reducing agent components of the redox initiator are added to deionized water, stirred and mixed evenly, and then heated to 30-50 °C under inert atmosphere, and half of the oxidant component of the redox initiator is slowly added to react for 1-3 h; then the other half of the oxidant and reducing agent components of the redox initiator are slowly added to react for 2-10 h; the temperature is raised to 60-80 °C and reacted for 1-3 h to obtain the target product - an ionomer solution with self-healing function, the solid content of which is 10-30 wt%.
[0014] Then, the self-repairing functional ionomer solution prepared above was diluted with deionized water and ethanol to a solid content of 2-10 wt%, and the self-repairing functional ionomer was deposited on the exposed copper current collector by electrophoretic deposition. The electrophoresis voltage was controlled to be 0.4-1.2 V, and the electrophoresis time was 240-420 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer.
[0015] The third aspect of the present invention provides a negative electrode-free lithium metal battery, including a copper-based current collector modified with a self-healing artificial interface layer, while other components, including a lithium-rich positive electrode, a separator and an electrolyte, are not particularly limited.
[0016] Compared with the prior art, the beneficial effects of the present invention include at least:
[0017] (1) The two hydroxyl groups in the catechol group of the dopamine-based self-healing monomer can participate in the formation of multiple hydrogen bonds, allowing the artificial interface layer to be repaired in time after being damaged by lithium dendrites, which helps to improve the cycle life and rate performance of the battery.
[0018] (2) Double-bond terminated polyethylene oxide can form a uniform lithium ion migration channel, improve the ionic conductivity of the artificial interface layer, and improve the rate performance of the battery; and enhance the flexibility of the polymer chain, so that the artificial interface layer can adapt to the cyclic strain caused by repeated lithium deposition and stripping, thereby extending the cycle life of the battery.
[0019] (3) Quaternary ammonium salt monomers contain ionizable cationic groups, which makes it possible to construct an artificial interface layer by electrophoretic deposition. This helps to form an artificial interface layer with controllable thickness and good density, and plays the role of cationic ionomers in homogenizing the electric field.
[0020] (4) Nitrogen-containing water-soluble comonomers not only help other functional monomers to form copolymers to exert the synergistic effect of each component, but the nitrogen element they contain can also promote the formation of a stable SEI, thereby comprehensively improving the electrochemical performance of negative electrode-free lithium metal batteries.
[0021] Figure 1 The scanning electron microscope images at a magnification of 200 times show scratches on the surface of the copper-based current collector modified with the self-repairing artificial interface layer described in Example 1 at different self-repairing times.
[0022] Figure 2 The LiNi assembled by Example 1 and Comparative Examples 1, 2 and 3 0.8 Co 0.1 Mn 0.1 Cycling performance of O2 ternary cathode||copper full battery under constant current charge and discharge at 0.5 C rate.
[0023] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with embodiment. It should be understood by those skilled in the art that the embodiment is only to help understand the present invention and should not be regarded as a specific limitation of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.
[0024] Example 1.
[0025] In this embodiment, a copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery includes:
[0026] 2.0 g acrylamide, 3.4 g methacryloyloxyethyl trimethylammonium chloride, 4.5 g polyethylene glycol monomethyl ether methacrylate, 0.08 g 3-methacrylamide dopamine and 0.04 g sodium bisulfite were added to deionized water, stirred and mixed evenly, and then heated to 50 °C under argon protection, and 0.08 g ammonium persulfate was slowly added and reacted for 3 h; then 0.04 g sodium bisulfite and 0.08 g ammonium persulfate were slowly added and reacted for 2 h; the temperature was raised to 60 °C and reacted for 1 h to obtain the target product - an ionomer solution with self-healing function, and the solid content of the ionomer solution was 20 wt%.
[0027] The prepared self-repairing ionomer solution was diluted with deionized water and ethanol to a solid content of 6 wt%, and the self-repairing ionomer was deposited on a bare copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 0.6 V and the electrophoresis time was 300 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. The thickness of the artificial interface layer is 5 um.
[0028] The applicant further assembled the copper-based current collector modified by the self-repairing artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery. 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material powder, LiNiO2 lithium nickelate powder, conductive carbon black particles and polyvinylidene fluoride emulsion binder are dispersed in N-methylpyrrolidone at a mass ratio of 77:19:2:2, and the mixture is ground until the particles are evenly dispersed to obtain a positive electrode slurry. The positive electrode slurry is then coated on aluminum foil and dried overnight at 100 ° C in a vacuum oven, and punched into a circular sheet with a diameter of 12 mm to prepare a positive electrode sheet.
[0029] The applicant examined the obtained self-repairing polymer modified copper-based current collector under a microscope and obtained Figure 1 The self-repairing ionomer described in Example 1 exhibits excellent self-repairing performance in a short time, which has a significant effect on the timely repair of the subsequent artificial interface layer.
[0030] Example 2.
[0031] In this embodiment, a copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery includes:
[0032] Take 4.5 g of N-methyl methacrylamide, 2.0 g of methacryloyloxypropyl trimethyl ammonium chloride, 3.0 g of polyethylene glycol monomethyl ether methacrylate, 0.05 g of 3-methacrylamide dopamine and 0.024 g of sodium thiosulfate, add them into deionized water, stir and mix evenly, then under argon protection, heat to 30 °C, slowly add 0.024 g of potassium persulfate, and react for 3 h; then slowly add 0.024 g of sodium thiosulfate and 0.024 g of potassium persulfate, and react for 6 h; heat to 70 °C, react for 3 h, and obtain the target product - an ionomer solution with self-healing function, the solid content of which is 10 wt%.
[0033] The prepared self-repairing ionomer solution was diluted with deionized water and ethanol to a solid content of 2 wt%, and the self-repairing ionomer was deposited on a bare copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 0.8 V and the electrophoresis time was 420 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. The thickness of the artificial interface layer is 8 um.
[0034] The applicant further assembled the copper-based current collector modified by the self-repairing artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery, and the preparation of the positive electrode material was the same as in Example 1.
[0035] Example 3.
[0036] In this embodiment, a copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery includes:
[0037] Take 2.0 g of methacrylamide, 4.0 g of acryloyloxyethyl trimethylammonium chloride, 4.0 g of polyethylene glycol monomethyl ether methacrylate, 0.06 g of 3-methacrylamide dopamine and 0.075 g of sodium bisulfite and add them to deionized water. After stirring and mixing evenly, under argon protection, the temperature is raised to 40 ° C, and 0.075 g of ammonium persulfate is slowly added and reacted for 1 h; then 0.075 g of sodium bisulfite and 0.075 g of ammonium persulfate are slowly added and reacted for 10 h; the temperature is raised to 80 ° C and reacted for 2 h to obtain the target substance - an ionomer solution with self-healing function, and the solid content of the ionomer solution is 30wt%.
[0038] The prepared self-repairing ionomer solution was diluted with deionized water and ethanol to a solid content of 10 wt%, and the self-repairing ionomer was deposited on a bare copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 0.4 V and the electrophoresis time was 420 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. The thickness of the artificial interface layer is 9 um.
[0039] The applicant further assembled the copper-based current collector modified by the self-repairing artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery, and the preparation of the positive electrode material was the same as in Example 1.
[0040] Example 4.
[0041] In this embodiment, a copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery includes:
[0042] 3.0 g of N-methyl methyl acrylamide, 3.0 g of methacryloyloxyethyl trimethyl ammonium chloride, 3.5 g of polyethylene glycol monomethyl ether methacrylate, 0.07 g of 3-methacrylamide dopamine and 0.035 g of sodium thiosulfate were added to deionized water, stirred and mixed evenly, and then heated to 50 °C under argon protection, and 0.075 g of potassium persulfate was slowly added and reacted for 2 h; then 0.035 g of sodium thiosulfate and 0.075 g of potassium persulfate were slowly added and reacted for 8 h; the temperature was raised to 65 °C and reacted for 1 h to obtain the target substance - an ionomer solution with self-healing function, and the solid content of the ionomer solution was 15 wt%.
[0043] The prepared self-repairing ionomer solution was diluted with deionized water and ethanol to a solid content of 4 wt%, and the self-repairing ionomer was deposited on a bare copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 1.2 V and the electrophoresis time was 240 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. The thickness of the artificial interface layer is 9 um.
[0044] The applicant further assembled the copper-based current collector modified by the self-repairing artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery, and the preparation of the positive electrode material was the same as in Example 1.
[0045] Example 5.
[0046] In this embodiment, a copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery includes:
[0047] Take 2.0 g of methacrylamide, 3.4 g of methacryloyloxyethyltrimethylammonium chloride, 4.5 g of polyethylene glycol monomethyl ether methacrylate, 0.09 g of 3-methacrylamide dopamine and 0.04 g of sodium thiosulfate and add them to deionized water. After stirring and mixing evenly, under argon protection, the temperature is raised to 50 ° C, and 0.08 g of potassium persulfate is slowly added and reacted for 3 h; then 0.04 g of sodium thiosulfate and 0.08 g of potassium persulfate are slowly added and reacted for 2 h; the temperature is raised to 60 ° C and reacted for 1 h to obtain the target substance - an ionomer solution with self-healing function, and the solid content of the ionomer solution is 20wt%.
[0048] The prepared self-repairing ionomer solution was diluted with deionized water and ethanol to a solid content of 6 wt%, and the self-repairing ionomer was deposited on a bare copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 0.6 V and the electrophoresis time was 360 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. The thickness of the artificial interface layer was 10 um.
[0049] The applicant further assembled the copper-based current collector modified by the self-repairing artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery, and the preparation of the positive electrode material was the same as in Example 1.
[0050] Example 6.
[0051] In this embodiment, a copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with a self-repairing artificial interface layer for a negative-electrode lithium battery includes:
[0052] 2.0 g acrylamide, 3.4 g methacryloyloxyethyl trimethylammonium chloride, 4.5 g polyethylene glycol monomethyl ether methacrylate, 0.1 g 3-methacrylamide dopamine and 0.04 g sodium thiosulfate were added to deionized water, stirred and mixed evenly, and then heated to 50 °C under argon protection, and 0.08 g potassium persulfate was slowly added and reacted for 3 h; then 0.04 g sodium thiosulfate and 0.08 g potassium persulfate were slowly added and reacted for 2 h; the temperature was raised to 60 °C and reacted for 1 h to obtain the target substance - an ionomer solution with self-healing function, and the solid content of the ionomer solution was 20 wt%.
[0053] The prepared self-repairing ionomer solution was diluted with deionized water and ethanol to a solid content of 6 wt%, and the self-repairing ionomer was deposited on the exposed copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 0.6 V and the electrophoresis time was 300 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. This ratio cannot achieve electrophoretic deposition.
[0054] The applicant further assembled the copper-based current collector modified by the self-repairing artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery, and the preparation of the positive electrode material was the same as in Example 1.
[0055] Comparative Example 1
[0056] Comparative Example 1 A positive electrode sheet was obtained by referring to the positive electrode material preparation method in the above-mentioned Example 1, but the ionomer solution was not deposited when preparing the negative electrode current collector, and only a bare copper-based current collector was used for the negative electrode. The assembled negative electrode-free lithium battery was used as a test sample.
[0057] Comparative Example 2.
[0058] Comparative Example 2 The ionomer was obtained by referring to the self-healing ionomer synthesis method in Example 1 and the positive electrode material preparation method to obtain the positive electrode sheet, but when preparing the negative electrode, a 10 um scraper was used to evenly apply the ionomer solution on the copper-based current collector, and the assembled negative electrode-free lithium battery was used as a test sample.
[0059] Comparative Example 3.
[0060] In this comparative example, a copper-based current collector modified with an artificial interface layer for a negative-electrode lithium battery is provided. The preparation method of the copper-based current collector modified with an artificial interface layer for a negative-electrode lithium battery includes:
[0061] Take 2.0 g of acrylamide, 3.4 g of methacryloyloxyethyl trimethylammonium chloride, 4.5 g of polyethylene glycol monomethyl ether methacrylate and 0.04 g of sodium bisulfite and add them to deionized water. After stirring and mixing evenly, under argon protection, heat it to 50 ° C, slowly add 0.08 g of ammonium persulfate, and react for 3 h; then slowly add 0.04 g of sodium bisulfite and 0.08 g of ammonium persulfate, and react for 2 h; heat it to 60 ° C, react for 1 h, and obtain the target product - ionomer solution, the solid content of which is 20 wt%.
[0062] The prepared ionomer solution was diluted with deionized water and ethanol to a solid content of 6 wt%, and the ionomer was deposited on a bare copper-based current collector by electrophoresis, with the copper electrode as the cathode and the stainless steel sheet as the anode. The electrophoresis voltage was controlled to be 0.6 V and the electrophoresis time was 300 s to obtain a copper-based current collector modified with a self-repairing artificial interface layer. The thickness of the artificial interface layer was 7 um.
[0063] The applicant further assembled the copper-based current collector modified by the artificial interface layer of this embodiment and the positive electrode into a negative electrode-free lithium battery, and the preparation of the positive electrode material was the same as in Example 1.
[0064] Figure 2 As shown, the LiNi prepared in Example 1 of the present invention and Comparative Examples 1-3 0.8 Co 0.1 Mn 0.1 The specific capacity and coulombic efficiency curve of the O2 ternary positive electrode material||copper full battery after 100 charge and discharge cycles under the condition of current density of 0.5 C (charge / discharge rate), the coulombic efficiency of Example 1 is maintained at 99%, and the capacity retention rate is 47%. The cycle performance of the full battery assembled with the copper-based current collector negative electrode with a self-healing functional interface layer described in Example 1 is better, significantly better than that of Comparative Examples 1-3, mainly because the ionomer deposited by electrophoresis can promote the transmission of lithium ions, inhibit the growth of lithium dendrites and perform self-repair in time, thus having a positive effect on improving the cycle performance of the full battery.
[0065] In the above embodiments and comparative examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0066] Verification example: The self-healing efficiency, room temperature ionic conductivity, and tensile strength of the ionomers described in Examples 1-6 and Comparative Examples 1-3 were tested to obtain the test results shown in Table 1.
[0067] Self-healing efficiency: The ionomer was dried at 100 °C to form a film, and then cut into dumbbell-shaped specimens of 15 mm long × 2 mm wide. The sample was fixed between the upper and lower clamps of the universal testing machine along the length direction. The lower clamp was immobile, and the upper clamp was stretched at a constant rate of 20 mm / min until the sample broke, and the stress was recorded as σ1; a scratch was made at the thinnest part of another similar specimen with a carving knife, and it was transferred to the mold and left to stand for self-healing. After 2 h, the self-healed specimen repeated the above tensile test, and the stress was recorded as σ2. Self-healing efficiency = (σ2-σ1) / σ1×100%.
[0068] Ionic conductivity: The ionomer was dried at 100 °C to form a film, which was cut into a disc with a diameter of 12 mm. The disc was sandwiched between two stainless steel gaskets to assemble into a symmetrical cell, and an AC impedance test was performed. The ionic conductivity at room temperature (25 °C) was calculated and shown in Table 1.
[0069] Tensile strength: universal testing machine; tensile mode test. The self-healing artificial interface layer was dried at 100 °C and cut into dumbbell-shaped specimens of 15 mm long × 2 mm wide. The sample was fixed between the upper and lower clamps of the universal testing machine along the length direction. The lower clamp was fixed and the upper clamp was stretched at a constant rate of 20 mm / min until the sample broke. The stress was recorded as σ.
[0070] Table 1 Physical properties of ionomers sample Self-repair efficiency (%) <![CDATA[Ionic conductivity (S cm -1 ).]]> Tensile strength (MPa) Example 1 95 <![CDATA[1.39×10 -3 ]]> 11.5 Example 2 96 <![CDATA[1.35×10 -3 ]]> 11.7 Example 3 85 <![CDATA[0.82×10 -3 ]]> 9.5 Example 4 88 <![CDATA[0.92×10 -3 ]]> 10.2 Example 5 92 <![CDATA[0.88×10 -3 ]]> 10.8 Example 6 93 <![CDATA[1.28×10 -3 ]]> 11.2 Comparative Example 1 ----- ----- ----- Comparative Example 2 87 <![CDATA[0.73×10 -3 ]]> 7.5 Comparative Example 3 1 <![CDATA[0.87×10 -3 ]]> 6.8 From the data in Table 1, it can be seen that the self-healing efficiency of the ionomers described in Examples 1-6 is 82%~95%, and the ionic conductivity can reach 0.82~1.39 x10 -3 S cm -1 , mechanical strength 8.6~11.5 MPa. And with the increase of dopamine self-repairing monomers, the self-repairing efficiency and tensile strength of the interface layer gradually increase. However, when the weight of the self-repairing monomer is 0.9 wt%, the viscosity of the system is too large, which is not conducive to the implementation of subsequent steps. Although the self-repairing rate and mechanical strength are the highest when the weight of the self-repairing monomer is 1 wt%, the subsequent electrophoretic deposition process cannot be carried out because gelation occurs at this ratio. It can also be found from the table that double-bond terminated polyethylene oxide can improve the ionic conductivity of the interface layer. In Comparative Example 1, there is no artificial interface layer, so there is no self-repairing property; the artificial interface layer prepared by scraping in Comparative Example 2 has a self-repairing rate of 87%, and the ionic conductivity and mechanical strength are lower than those of the artificial interface layer obtained by electrophoretic deposition. This is because the electrophoretic deposition process helps the regular arrangement of molecular chains, thereby improving the uniformity and electrochemical properties of the interface layer. In Comparative Example 3, the failure to add a self-repairing monomer not only leads to the almost loss of self-repairing property, but also reduces the mechanical strength, and the ionic conductivity of the interface layer also decreases slightly.
[0071] The copper-based current collectors with self-repairing functional interface layers prepared in Examples 1-6 and Comparative Examples 1-3 were cut into discs with a diameter of 12 mm, and their masses and thicknesses were recorded. The test results shown in Table 2 were obtained.
[0072] Table 2 Mass and thickness of self-repairing functional interface layer sample Mass (mg) Thickness (um) Example 1 9.2 5 Example 2 9.7 8 Example 3 10.1 9 Example 4 10.2 9 Example 5 11.2 10 Example 6 ---- ---- Comparative Example 1 8.8 0 Comparative Example 2 9.2 5 Comparative Example 3 9.5 7 It can be seen from the data in Table 2 that the composition of the polymer, the time and voltage of electrophoresis will affect the quality and thickness of the interface layer. The thickness of the interface layer in Example 1 is only 5 um. When the weight of the dopamine self-healing monomer is 1 wt%, due to the gelation phenomenon, the polymer will aggregate unevenly on the copper-based current collector, and a uniform electrophoretic deposition process cannot be performed.
[0073] For the LiNi2O3 negative electrodes assembled with different copper-based current collectors described in Examples 1-6 and Comparative Examples 1-3, 0.8 Co 0.1 Mn 0.1 The O2 ternary positive electrode||copper full battery was subjected to charge and discharge performance tests and cycle performance tests, and the test results shown in Table 3 were obtained.
[0074] Table 3 LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary cathode||discharge capacity and coulombic efficiency of copper full battery sample <![CDATA[Discharge capacity at 0.1C (mAh g -1 ).]]> Coulomb efficiency after 100 cycles (%) Example 1 220 99 Example 2 170 90 Example 3 186 89 Example 4 198 92 Example 5 201 98 Example 6 ---- ---- Comparative Example 1 164 9 Comparative Example 2 188 85 Comparative Example 3 178 48 It can be seen from the data in Table 3 that the LiNi 0.8 Co 0.1 Mn 0.1 The first discharge capacity of the O2 ternary positive electrode||copper full battery is significantly higher than that of Comparative Examples 1-3. At the same time, the LiNi 0.8 Co 0.1 Mn 0.1 After 100 cycles of the O2 ternary positive electrode||copper full battery, the coulombic efficiency is above 89%, which is significantly higher than the highest value of Comparative Examples 1 to 3. This proves that the invention can facilitate the rapid transmission of lithium ions at high current density by introducing a self-repairing artificial interface layer, thereby increasing the amount of lithium involved in the reaction and improving the specific capacity of the battery at high current density.
[0075] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, modifications and equivalent settings contained in the spirit and scope of the claims are all included in the scope of the present invention.
Claims
1. A copper-based current collector modified with a self-repairing artificial interface layer, characterized in that: It is obtained by modifying a self-repairing ionomer on a bare copper-based current collector through solution polymerization of four components A, B, C, and D, wherein component A is a nitrogen-containing water-soluble comonomer, which is 20 to 45 parts by weight; component B is a quaternary ammonium salt monomer, which is 20 to 40 parts by weight; component C is a double-bond terminated polyethylene oxide, which is 30 to 45 parts by weight; component D is a dopamine self-repairing monomer, which is 0.5 to 1.0 parts by weight. The thickness of the self-repairing artificial interface layer is 5 to 10 µm. The copper-based current collector modified with the self-repairing artificial interface layer is prepared by the following preparation method: (1) A nitrogen-containing water-soluble comonomer, a quaternary ammonium salt monomer, a double-bond-terminated polyethylene oxide and a dopamine self-healing monomer and part of the reducing agent component of the redox initiator are added to deionized water, stirred and mixed evenly, and then heated to 30-50 °C under an inert atmosphere, and half of the oxidant component of the redox initiator is slowly added, and the reaction is carried out for 1-3 h; then the other half of the oxidant and reducing agent components of the redox initiator are slowly added, and the reaction is carried out for 2-10 h; the temperature is raised to 60-80 °C, and the reaction is carried out for 1-3 h to obtain the target product, that is, an ionomer solution with self-healing function, wherein the solid content of the ionomer solution is 10-30 wt%. (2) The self-healing ionomer solution prepared in step (1) is diluted with deionized water and ethanol to a solid content of 2-10 wt %, and the self-healing ionomer is deposited on a bare copper current collector by electrophoretic deposition. The electrophoretic voltage is controlled to be 0.4-1.2 V, and the electrophoresis time is controlled to be 240-420 s to obtain a copper-based current collector modified with a self-healing artificial interface layer.
2. The copper-based current collector modified with a self-repairing artificial interface layer and the preparation method thereof according to claim 1, characterized in that: The nitrogen-containing water-soluble comonomer is one of acrylamide, N-methyl methacrylamide and methacrylamide.
3. The copper-based current collector modified with a self-repairing artificial interface layer and the preparation method thereof according to claim 1, characterized in that: The quaternary ammonium salt monomer is one of methacryloyloxyethyl trimethyl ammonium chloride, methacryloyloxypropyl trimethyl ammonium chloride and acryloyloxyethyl trimethyl ammonium chloride.
4. The copper-based current collector modified with a self-repairing artificial interface layer and the preparation method thereof according to claim 1, characterized in that: The double-bond terminated polyethylene oxide is polyethylene glycol monomethyl ether methacrylate.
5. The copper-based current collector modified with a self-repairing artificial interface layer and the preparation method thereof according to claim 1, characterized in that: The dopamine self-repairing monomer is 3-methacrylamide dopamine.
6. The copper-based current collector modified with a self-repairing artificial interface layer and the preparation method thereof according to claim 1, characterized in that: The oxidant component of the redox initiator is preferably one of ammonium persulfate and potassium persulfate; the reducing agent component is preferably one of sodium bisulfite and sodium thiosulfate; the mass ratio of the oxidant component to the reducing agent component is 1:0.5~1:
1.
7. The copper-based current collector modified with a self-repairing artificial interface layer and the preparation method thereof according to claim 1, characterized in that: The amount of the redox initiator used in the preparation method is 1.0 wt% to 3.0 wt% of the total amount of the four component monomers.
8. Use of the copper-based current collector modified with the self-repairing artificial interface layer according to any one of claims 1 to 7 in a negative electrode-free lithium battery.
Citation Information
Patent Citations
Lithium-free negative pole piece, preparation method thereof and lithium battery
CN117438533A
Negative current collector with DNA interface layer and negative-electrode-free lithium metal battery
CN118198375A
Lithium metal negative electrode material, preparation method and application thereof
CN110474053A
Copper surface modification method based on polydopamine
CN113260172A
Silver particle coating modified three-dimensional porous copper current collector-lithium negative electrode integrated structure as well as preparation method and application thereof
CN113937269A
Cited By
Preparation method and application of composite current collector with self-repairing functional film
CN122202178A
Preparation method and application of a composite current collector with self-healing membrane
CN122202178B